Study of the fatigue curve in quadriceps and hamstrings of soccer players during isokinetic endurance testing - Sangnier, S.; Tourny-Chollet, C. (The Journal of Strength and Conditioning Research, 2008)
Many studies have presented regression models of quadriceps (Q) muscle strength loss with fatigue development. Paradoxically, the hamstrings (H), which are the principal site of muscle injury in soccer players, have received little attention, and no regression model has been established. This study investigated strength loss in the Q and H to establish a regression model using the lowest number of flexions-extensions during isokinetic endurance testing. Twenty-four semiprofessional soccer players performed 50 flexion-extension movements at 180°/s on an isokinetic dynamometer. The theoretical equations were calculated from the first 10, first 15, first 20, and first 25 contractions for each muscle group by several regression models (linear, quadratic, cubic). The linear model was the best fit to this exercise protocol to describe the strength loss in both muscle groups. The quadratic model was the best fit to predict the changes in the H/Q ratio. This study showed that a regression model can be established for both muscle groups. A minimum of 20 extensions and 15 flexions was needed to establish a linear model that represented strength loss in, respectively, Q and H. A minimum of 25 flexions-extensions was needed with the quadratic model to accurately determine the decrease in the H/Q ratio. Isokinetic endurance testing can be carried out with only 25 flexions-extensions. This reduction should facilitate the implementation of this protocol. Regular evaluation would contribute to the efforts to prevent muscle injury during competitive sports activity.